Pengaruh Kedisiplinan dan Motivasi terhadap Produktivitas Kerja pegawai pada Kantor Badan Kepegawaian Pendidikan dan Pelatihan (BKPP) Kabupaten Polewali Mandar - Jasnika Jasnika; Romansyah Sahabuddin; Uhud Darmawan Natsir; Agung Widhi Kurniawan; Zainal Ruma (Jurnal Visi Manajemen, 2026)
This study aims to determine the effect of discipline and motivation on employee work productivity at the Office of the Personnel, Education, and Training Agency (BKPP) of Polewali Mandar Regency, both partially and simultaneously. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to all 43 employees of the BKPP Office of Polewali Mandar Regency. The analytical technique used was multiple linear regression to examine the relationship between the variables of discipline, motivation, and work productivity.The results of the study indicate that motivation has a significant effect on employee work productivity. Employees with high motivation tend to demonstrate greater enthusiasm, a strong sense of responsibility, and optimal performance achievement. Conversely, discipline does not show a significant effect when observed separately, but it still plays an important role when combined with motivation. The combination of discipline and motivation has been proven to enhance overall work productivity. Motivation significantly influences employee work productivity, whereas discipline does not have a partial effect. However, together, discipline and motivation contribute to improving employee work productivity at the BKPP Office of Polewali Mandar Regency.